2011
DOI: 10.1001/archinternmed.2011.170
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Anticholinergic Drug Therapy and the Risk of Acute Urinary Retention in Chronic Obstructive Pulmonary Disease

Abstract: Use of short- and long-acting IACs is associated with an increased risk of AUR in men with COPD. Men receiving concurrent treatment with both short- and long-acting IACs and those with evidence of benign prostatic hyperplasia are at highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 29 publications
(33 reference statements)
1
51
0
2
Order By: Relevance
“…The authors found (using multivariable conditional logistic regression) that new users of inhaled anticholinergics were significantly more likely to have sought medical care for acute urinary retention (OR 1.42; 95% CI 1.20-1.68) [Stephenson et al 2011]. However, as with Afonso's study above [Afonso et al 2011], the association of inhaled anticholinergics was less apparent when considering past users.…”
Section: Observational Studiesmentioning
confidence: 89%
“…The authors found (using multivariable conditional logistic regression) that new users of inhaled anticholinergics were significantly more likely to have sought medical care for acute urinary retention (OR 1.42; 95% CI 1.20-1.68) [Stephenson et al 2011]. However, as with Afonso's study above [Afonso et al 2011], the association of inhaled anticholinergics was less apparent when considering past users.…”
Section: Observational Studiesmentioning
confidence: 89%
“…While patients with severe COPD have a limited ability to sustain a bronchodilation, increasing blood flow to poorly ventilated lung regions causes a ventilation-perfusion mismatch. 21,22,24 Nebulized furosemide may reverse that pathological process by improving ventilation, particularly in patients who require higher doses of ␤ 2 -adrenoceptor agonists.…”
Section: Discussionmentioning
confidence: 99%
“…c o m / l o c a t e / l i f e s c i e aclidinium bromide at therapeutic doses in patients with COPD . The relatively high incidence of urinary difficulty and urinary retention reported for tiotropium in clinical practice (Kesten et al, 2006;Stephenson et al, 2011;Tashkin, 2009) prompted us to study the renal and urinary safety profile of aclidinium in preclinical animal models.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 99%
“…Both drugs are considered to be relatively safe agents; however, they both have been associated with systemic anticholinergic side effects including dry mouth, constipation, blurred vision, glaucoma, urinary retention/difficulty and increased heart rate (Boehringer Ingelheim International GmbH, 2008a, 2008b. Recent studies have highlighted the risk of acute urinary retention (AUR) with current therapies in patients with COPD (Stephenson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%